Building Bridges 2.0 Between the History and the Maritime Heritage and the Virtual Users: The Blog and the Facebook Profile of the Naval History Chair - Martinez Solis, Lorena; Chaín Navarro, Celia; Sánchez Baena, Juan José; Díaz Pérez, Fernando (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
The Naval History Chair, driven by the Spanish Navy and the University of Murcia, it has among its objectives to investigate and disseminate the History and the Naval and Maritime Heritage. In order to bring scientific knowledge and information about these themes to the user, our institution not only uses the classic communication channels such as articles and monographs, among others, but, in its commitment to the Digital Humanities, it makes a proactive use of a blog and a social networks profiles which, apparently, make us contact effectively with the virtual reader. In order that we continue improving, through this work, we analyze what issues have aroused greater interest among the readers of our social tolos, through the study of the publications of our blog and the reflection of these in our Facebook page. The answer will help us to better understand the interests and information needs of the users, as a result, we´ll can further devolpt the digital bridges that we have layed between the and the History and the Naval and Maritime Heritage.